Comparison of the Core-collapse Evolution of Two Nearly Equal-mass Progenitors - Stephen W. Bruenn; Andre Sieverding; Eric J. Lentz; Tuguldur Sukhbold; W. Raphael Hix; Leah N. Huk; J. Austin Harris; O. E. Bronson Messer; Anthony Mezzacappa (The Astrophysical Journal, 2023)
We compare the core-collapse evolution of a pair of 15.8 M _☉ stars with significantly different internal structures, a consequence of the bimodal variability exhibited by massive stars during their late evolutionary stages. The 15.78 and 15.79 M _☉ progenitors have core masses (masses interior to an entropy of 4 k _B baryon ^−1 ) of 1.47 and 1.78 M _☉ and compactness parameters ξ _1.75 of 0.302 and 0.604, respectively. The core-collapse simulations are carried out in 2D to nearly 3 s postbounce and show substantial differences in the times of shock revival and explosion energies. The 15.78 M _☉ model begins exploding promptly at 120 ms postbounce when a strong density decrement at the Si–Si/O shell interface, not present in the 15.79 M _☉ progenitor, encounters the stalled shock. The 15.79 M _☉ model takes 100 ms longer to explode but ultimately produces a more powerful explosion. Both the larger mass accretion rate and the more massive core of the 15.79 M _☉ model during the first 0.8 s postbounce time result in larger ν _e / ${\bar{ν }}_{e}$ luminosities and RMS energies along with a flatter and higher-density heating region. The more-energetic explosion of the 15.79 M _☉ model resulted in the ejection of twice as much ^56 Ni. Most of the ejecta in both models are moderately proton rich, though counterintuitively the highest electron fraction ( Y _e = 0.61) ejecta in either model are in the less-energetic 15.78 M _☉ model, while the lowest electron fraction ( Y _e = 0.45) ejecta in either model are in the 15.79 M _☉ model.